2005
DOI: 10.1093/jac/dki160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ambler class A and D β-lactamases among clinical isolates of Pseudomonas aeruginosa in Korea

Abstract: OXA-type beta-lactamases are widespread, but their extended-spectrum derivatives are rare among P. aeruginosa in Korea. To our knowledge, this is the first report of OXA-17, an extended-spectrum derivative of OXA-10, outside the Middle East. In addition, combined resistance to ticarcillin and aminoglycosides was a useful indicator for P. aeruginosa producing PSE- or OXA-type beta-lactamases in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 27 publications
4
67
2
Order By: Relevance
“…DNA extraction was performed by the simple boiling method of bacterial colonies from all isolates that were identified as P. aeruginosa by phenotypic criteria (13).…”
Section: Polymerase Chain Reaction Amplification Of the Mexa And Mexbmentioning
confidence: 99%
“…DNA extraction was performed by the simple boiling method of bacterial colonies from all isolates that were identified as P. aeruginosa by phenotypic criteria (13).…”
Section: Polymerase Chain Reaction Amplification Of the Mexa And Mexbmentioning
confidence: 99%
“…The bla SHV and bla TEM were amplified as described previously [5]. Plasmid DNA was extracted by miniprep kit (Metabion, Martinsried, Germany) and targeted for the bla CTX-M gene using the primers described by Lee et al [12] under the following conditions: 94°C for 3 minutes, and 35 cycles of 94°C for 30 seconds, 63°C for 1 minute, 72°C for 1 minute and a final extension in 72°C for 10 minutes. K. pneumoniae ATCC 700603, E. coli ATCC 35218 and K. pneumoniae 7881 were used as positive controls for bla SHV , bla TEM and bla CTX-M , respectively.…”
Section: Pcr Amplification Of Beta-lactamase Genesmentioning
confidence: 99%
“…Farshadzadeh et al, in a study carried out at the Taleghani Burn Hospital in Ahvaz (Iran), reported that 54.2% and 68.7% of ESBL-producing isolates of P. aeruginosa harbored bla PER-1 and bla OXA-10 , respectively 29 . Among the studies reported from Asian countries, Lee and colleagues from South Korea showed that 6.3%, 13.1%, 4.3%, 2.0%, 2.3%, and 0.4% of P. aeruginosa isolates carried the bla PSE-1 , bla , bla OXA-4 , bla OXA-30 , bla OXA-2 , and bla OXA-17 genes, respectively 36 . In another study performed in Saudi Arabia, the presence of genes encoding VEB-1, OXA-10, and GES was confirmed among extended-spectrum cephalosporin-non-susceptible P. aeruginosa clinical isolates from burn patients 10 .…”
mentioning
confidence: 99%